Crystal Structure, Physical Properties and HRTEM Investigation of the New Oxonitridosilicate EuSi2O2N2 - Stadler, Florian; Oeckler, Oliver; Höppe, Henning A.; Möller, Manfred H.; Pöttgen, Rainer; Mosel, Bernd D.; Schmidt, Peter; Duppel, Viola; Simon, Arndt; Schnick, Wolfgang (Chemistry : a European journal, 2006)
The new layered oxonitridosilicate EuSi2O2N2 has been synthesized in a radio‐frequency furnace at temperatures of about 1400 °C starting from europium(III) oxide (Eu2O3) and silicon diimide (Si(NH)2). The structure of the yellow material has been determined by single‐crystal X‐ray diffraction analysis (space group P1 (no. 1), a=709.5(1), b=724.6(1), c=725.6(1) pm, α=88.69(2), β=84.77(2), γ=75.84(2)°,V=360.19(9)×106 pm3, Z=4, R1=0.0631, 4551 independent reflections, 175 parameters). Its anionic Si2O2N22− layers consist of corner‐sharing SiON3 tetrahedra with threefold connecting nitrogen and terminal oxygen atoms. High‐resolution transmission electron micrographs indicate both ordered and disordered crystallites as well as twinning. Magnetic susceptibility measurements of EuSi2O2N2 exhibit Curie–Weiss behavior above 20 K with an effective magnetic moment of 7.80(5) μB Eu−1, indicating divalent europium. Antiferromagnetic ordering is detected at 4.5(2) K. EuSi2O2N2 shows a field‐induced transition with a critical field of 0.50(5) T. The four crystallographically different europium sites cannot be distinguished by 151Eu Mössbauer spectroscopy. The room‐temperature spectrum is fitted by one signal at an isomer shift of δ=−12.3(1) mm s−1 subject to quadrupole splitting of ΔEQ=−2.3(1) mm s−1 and an asymmetry parameter of 0.46(3). Luminescence measurements show a narrow emission band with regard to the four crystallographic europium sites with an emission maximum at λ=575 nm. Das neue schichtartig aufgebaute Oxonitridosilicat EuSi2O2N2 wurde in einem Hochfrequenzofen bei etwa 1400 °C aus Europium(III)‐oxid (Eu2O3) und Siliciumdiimid (Si(NH)2) hergestellt. Die Kristallstruktur der gelben Verbindung wurde mittels Einkristallröntgenstrukturanalyse bestimmt (Raumgruppe P1 (Nr. 1), a=709.5(1), b=724.6(1), c=725.6(1) pm, α=88.69(2), β=84.77(2), γ=75.84(2)°, V=360.19(9)⋅106 pm3, Z=4, R1=0.0631, 4551 unabhängige Reflexe, 175 Parameter). Die anionischen Si2O2N22−‐Schichten bestehen aus eckenverknüpften SiON3‐Tetraedern mit dreifach verbrückendem Stickstoff und terminalem Sauerstoff. Hochauflösende Transmissionselektronenmikroskopie (HRTEM) zeigt sowohl geordnete als auch ungeordnete Kristallite sowie Verzwillingung. Messungen der magnetischen Suszeptibilität von EuSi2O2N2 ergeben oberhalb von 20 K Curie‐Weiss‐Verhalten mit einem effektiven magnetischen Moment von 7.80(5) μB Eu−1, welches auf zweiwertiges Europium hinweist. Bei 4.5(2) K wird antiferromagnetische Ordnung detektiert. EuSi2O2N2 zeigt einen feldinduzierten Übergang mit einem kritischen Feld von 0.50(5) T. Die vier kristallographisch unterschiedlichen Europiumatome konnten durch 151Eu‐Mößbauer‐Spektroskopie nicht unterschieden werden. Das Raumtemperaturspektrum konnte durch ein Signal bei einer Isomerenverschiebung von δ=−12.3(1) mm s−1 gemäß einer Quadrupolaufspaltung von ΔEQ=−2.3(1) mm s−1 und einem Asymmetrieparameter von 0.46(3) angepasst werden. Lumineszenzmessungen zeigten eine bzgl. der vier kristallographischen Europiumlagen schmale Emissionsbande mit einem Maximum bei λ=575 nm. The new layered oxonitridosilicate EuSi2O2N2 has been synthesized at 1400 °C starting from Si(NH)2 and Eu2O3. The crystal structure (see picture), including the characteristic twin and antiphase boundaries, has been comprehensively characterized by single‐crystal X‐ray diffraction and high‐resolution transmission electron microscopy (HRTEM). Magnetic properties, Mössbauer spectra and luminescence measurements agree well with each other and confirm the valence state and coordination of Eu.